ОРГАНІЗАЦІЯ САМОСТІЙНОЇ РОБОТИ СТУДЕНТІВ У ВИВЧЕННІ КУРСУ «МЕТОДИКА НАВЧАННЯ МАТЕМАТИКИ» (Pedagogy of Higher and Secondary Education, 2012)
У статті розглянуто проблему організації ефективної самостійної роботи студентів. Наводиться поетапна схему організації самостійної роботи, в контексті використання дистанційного навчання. Описано роботу дистанційного курсу, який використовується для організації самостійної роботи студентів.Ключові слова: самостійна робота студентів, професійна компетентність, дистанційне навчання.  The problem of organization of effective independent work of students is examined in the article. The stage-by-stage chart of organization of independent work of students, in the context of the use of distance education, is given. The work of distance course, which is used for organization of independent work of student, is described.  Key words: independent work of students, professional competence, distance education.
Keywords: independent work of students; professional competence